2004
DOI: 10.1002/cvde.200306290
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis and Characterization of New β‐Diketonate Silver Complexes. Single‐Crystal Structures of (1,1,1,5,5,5‐Hexafluoro‐2,4‐pentadionato)(2,2′‐bipyridine)silver(I) and (1,1,1,5,5,5‐Hexafluoro‐2,4‐pentadionato)(N,N,N′,N′‐tetramethylethylenediamine)silver(I) and Their Use as MOCVD Precursors for Silver Films

Abstract: Thin film depositions of metallic silver were performed using metal±organic (MO) CVD on glass substrates using, as precursors, the two new compounds (1,1,1,5,5,5-hexafluoro-2,4-pentanedionato)(2,2¢-bipyridine)silver(I), [Ag(hfac)(bipy)] (1), and (1,1,1,5,5,5-hexafluoro-2,4-pentanedionato)(N,N,N¢,N¢-tetramethylethylenediamine)silver(I), [Ag(hfac)(tmeda)] (2). Both silver compounds were characterized by single-crystal X-ray diffraction (XRD) measurements, indicating that 1 exists as a dimeric species, and 2 as p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…38 As a consequence, the two metal ions are not interacting significantly. 21,39 However, given the fact that there are no bridging ligands holding together the dimer, a weak stabilizing interaction between the metal ions might be postulated. 40 In addition, intra-dimer π stacking appeared between the -hfac and -phen rings (the distances separating the centroids (C T ) † is Finally, the dimers stack along the a axis in a head-to-tail arrangement (Fig.…”
Section: 33mentioning
confidence: 99%
See 1 more Smart Citation
“…38 As a consequence, the two metal ions are not interacting significantly. 21,39 However, given the fact that there are no bridging ligands holding together the dimer, a weak stabilizing interaction between the metal ions might be postulated. 40 In addition, intra-dimer π stacking appeared between the -hfac and -phen rings (the distances separating the centroids (C T ) † is Finally, the dimers stack along the a axis in a head-to-tail arrangement (Fig.…”
Section: 33mentioning
confidence: 99%
“…Few examples of ALD of Ag coatings have also been reported previously. [20][21][22][23][24][25] In the cases where AA-CVD was used, nonenvironmentally friendly solvents, such as THF and toluene, were used in combination with organometallic precursors. 10,11,16 Concerning the design of Ag metalorganic precursors, previous works have introduced different systems, including β-diketonate adducts Ag(hfac))(L) 26 or Ag(fod)(L),…”
Section: Introductionmentioning
confidence: 99%
“…This allows the forming of complexes of various structural organization and dimension. In particular, for silver, fluorinated β-diketonate ligands were used for constructing coordination polymers with macroligands [ 5 , 6 ] or exo-N-donor synthons [ 7 , 8 ], stabilizing the multinuclear ethynide or thiolate clusters [ 9 , 10 , 11 ], and obtaining polymer, di- or mononuclear precursors [ 12 , 13 , 14 ] for chemical vapor deposition processes.…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, Ag coatings exhibit a rough morphology because their growth tends to proceed by a Volmer–Weber mechanism . Many silver complexes have been investigated as suitable precursors for the deposition of silver metal on metallic substrates, but only few show air and moisture stability and decomposition temperatures suitable for a convenient annealing. It was also found that, in some cases, the silver deposition that occurs by CVD may require the stabilization of the precursor by appropriate fictionalization of the ligand …”
Section: Introductionmentioning
confidence: 99%